Perancangan Sistem Informasi Rencana Kerja Anggaran Perusahaan (RKAP) Pada PTPN IV Kebun Marihat - ,; ,; , (Seminar Nasional Informatika (SENATIKA), 2024)
PTPN IV is a company operating in the agribusiness and agroindustry sectors. In running its business, PTPN IV manages two plantation commodity business segments, namely the palm oil commodity business segment and the tea commodity business segment. PTPN IV is a State-Owned Enterprise (BUMN) which has thirty plantation units that manage oil palm and tea cultivation. PTPN IV is also supported by one engineering manufacturing and construction business unit, namely a power machinery factory (PMT) and managing oil palm seed plantations. Every company has a company budget that must be spent. Here the data used for research is in the form of Company Budget Work Plan (RKAP) Salary-Allowance data. The budget is a container of company information used by management to make decisions. Budgets have a formal, systematic approach to implementing manager responsibilities in planning, coordination and supervision. In the process of managing salary-allowance budget data using Information System Design with the Microsoft Visio application. The information system is created so that budget data is stored safely and makes it easier to process, secure data recording and can save time on work and no longer carry out calculations manually. With the Information System for processing salary-allowance budget data, it is hoped that it will make it easier for PTPN IV Kebun Marihat to manage its activities.